USING THE ELEMENTS OF TRADITIONAL CULTURE IN THE TEACHING PROCESS FROM THE PERSPECTIVE OF ETHNOPEDAGOGY AND ETHNOLOGY - Slobodová Nováková, Katarína; Sirotová, Mariana; Urban, Martin; Boghana, Jerome (Journal of Education Culture and Society, 2021)
Aim. The presented study aims to briefly present the possibilities of using and implementing elements of traditional culture in the teaching processat primary and secondary schools in Slovakia. It points out all the aspects and factors that enter the educational process when using these elements. Concept. Regional education is beingappliedin the educational environment of schools in order to develop the children with the right stimuli. The aim of including knowledge and partial topics of traditional folk culture in teaching is mainly to motivate students and arouse their interest in the cultural heritage of their ancestorsand country. We use comparative methods to clarify the relationships between ethnology, pedagogy, ethnopedagogy, and their interconnection in the pedagogical process. We define the primary goals of regional education, methods, and forms of teaching regional education, focusing on interactive forms of teaching. Results and conclusion. The values and the importance of traditional culture should be assessed in terms of the functions of education and training ina broader societal perspective.Regional education should make a significant contribution to the transmission of culture in education. The research results indicate the need to implement ethnopedagogy into the current educational process at all levels of education and scientifically verify its success. Research restrictions. The main research problems or limitations are related to the factthat this subdiscipline has not yet received attention in Slovakia. Originality. The paper presents an original view of ethnopedagogy and regional education issues through the lens of ethnology and pedagogy and defines key subjects of interest focusing on Slovak/Central European needs and contexts.